Utilization of chicken skin into "chicharon" Lolita Yu Ago ; Estrella F. Alabastro, adviser. - Ago, Lolita Yu.; Alabastro, Estrella (1974)
The utilization of chicken skin into a snackfood item in the form of "chicharon" was studied and storage studies were conducted for 5 weeks on the product. Variables studied during the development of a standard procedure were the levels of brine concentration (3%, 5% and 7%) and temperature ranges for frying (150-160°C and 170-180°C). Results of the sensory evaluation indicated that the 5% salt level and frying temperature of 170-180°C gave the most acceptable product. Storage studies showed an increase in peroxide values and moisture contents of the samples with storage time. BHT was incorporated in some samples and this slowed down the rate of peroxide development. Polyethylene (0.006 inch thickness) proved to be a better packaging material than polypropylene (0.003 inch thickness) with respect to peroxide development and flavor and texture characteristics of the product. It took 5 weeks of storage before the stored samples with BHT were significantly different from the freshly prepared ones in flavor, while it took only the second week for samples without BH
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Chicke